Réponses

  • x22
  • Modérateur Junior
2014-10-14T19:36:07+02:00
Bonsoir,

B= (x+1)(3-2x) C'est la double distributivité:
=x*3+x*(-2x)+1*3+1*(-2x)
=3x-2x²+3-2x
=1x-2x²+3

C=(3y+5)(10+y)
=3y*10+3y*y+5*10+5*y
=30y+3y²+50+5y
=35y+3y²+50

Tu fais le D
2014-10-14T19:43:01+02:00
B = ( x + 1 ) ( 3 - 2x )
= x * 3 + x * ( - 2x ) + 1 * 3 + 1 * ( - 2x )
= 3x - 2x² + 3 - 2x
= - 2x² + x + 3

C = ( 3y + 5 ) ( 10 + y )
= 3y * 10 + 3y * y + 5 * 10 + 5 * y
= 30y + 3y² + 50 + 5y
= 3y² + 35y + 50

D = ( z - 2 ) ( 3 - z )
= z * 3 + z * ( - z ) - 2 * 3 - 2 * ( - z )
= 3z - z² - 6 + 2z
= - z² + 5z - 6